Th‐Pb ion probe dating of zoned hydrothermal monazite and its implications for repeated shear zone activity: An example from the Central Alps, Switzerland. Issue 4 (10th April 2017) - Bergemann, C.; Gnos, E.; Berger, A.; Whitehouse, M.; Mullis, J.; Wehrens, P.; Pettke, T.; Janots, E.
Abstract: Th‐Pb age dating of zoned hydrothermal monazite from alpine‐type fissures/clefts is a powerful tool for constraining polyphase deformation at temperatures below 350°C and presents an alternative to K/Ar and 40 Ar/ 39 Ar dating techniques for dating brittle tectonics. This study considers the relationship between cleft orientations in ductile shear zones and cleft mineral crystallization during subsequent brittle overprinting. In the Grimsel area, located in the Aar Massif of the Central Alps, horizontal clefts formed during a primary thrust dominated deformation, while younger and vertically oriented clefts developed during secondary strike‐slip movements. The change is due to a switch in orientation between the principal stress axes σ 2 and σ 3 . The transition is associated with monazite crystallization and chloritization of biotite at around 11.5 Ma. Quartz fluid inclusion data allow a link between deformation stages and temperatures to be established and indicate that primary monazite crystallization occurred in both cleft systems at 300–350°C. While cleft monazite crystallization ceases at ~11 Ma in inactive shear zones, monazite growth, and/or dissolution‐reprecipitation continues under brittle deformation conditions in vertical clefts during later deformation until ~7 Ma. This younger shear zone activity occurs in association with dextral strike‐slip movement of the Rhone‐Simplon fault system. With the exception of varying Th/U values correlated with the degree of oxidation, there is only limited compositional variation in the studied cleft monazites. Key Points: Zoned hydrothermal monazite dated through SIMS U‐Th‐Pb isotope measurements Dating of multiple low‐temperature deformation events in a shear zone Coeval deformation in the central Aar Massif and along the Rhone‐Simplon Line